Determining lean manufacturing effectiveness in Malaysia using hybrid interpretive structural and structural equation models - Ng, Tan Ching (2016)
Lean Manufacturing is well-known to pursue waste elimination and reducing non-value added activities in the manufacturing industry. In Malaysia, lean manufacturing is still yet to be considered as mature state as there are still many private manufacturing companies in Malaysia that are not applying lean system or implementing partial lean. The lack of full-blown and widespread use of LM in Malaysia can be potentially due to many factors such as lack awareness in lean and not knowing the appropriate steps to apply lean in organizations, the research theme that is not well-studied yet. Therefore,it is important to discover the proper steps and important key determinants to effective implementation of LM in Malaysia in order to serve as guiding reference to the current and future lean implementers. By constructing the relationship model of key determinant of LM effectiveness, different lean practices and business performance index, the present study helps manufacturers to have an in-depth understanding of effective lean implementation process that obviously lead to an effective lean outcome. The study begins with the review of a number of reputable journal papers in LM context and then proceed with the interview with a Lean awarded company, in order to obtain the key determinants of LM effectiveness based on their professional perception. The qualitative analysis tool, Interpretive Structural Modelling is used to determine the sequence of key determinants based on the data collected from the interview. This study continued with the questionnaire-based survey of 160 Malaysian manufacturers and analysing the proposed research model of LM effectiveness using Partial Least Square-Structural Equation Modelling. Last but not least, the lean effectiveness model is further validated in a case study company in Malaysia to verify its reliability and applicability. The study concluded that there are seven top key determinants of LM effectiveness that will affect the successful implantation of LM in Malaysia, which are Investment cost, Teamwork, Information technology, Employee empowerment,Employee Involvement, Awareness of latest lean information, and Managerial Leadership and Support. These key determinants are showing essential influence over LM effectiveness when they are being applied with the proper precedence relationship in the organization. By implementing key determinants with proper sequence in the organization, an effective LM system could lead to a significant improvement in the different dimensions of business performance such as operation, marketing and financial dimensions. The results in effect showed that among Malaysian manufactures surveyed, 47% of improvement in business performance has been due the effective implementation of LM. The model developed offers important theoretical and practical implications to the manufacturers in Malaysia in order to improve the level of effective lean outcome.